2020
DOI: 10.3390/molecules25092103
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antibacterial Activity and Efflux Pump Reversal of Thymol and Carvacrol against Staphylococcus aureus and Their Toxicity in Drosophila melanogaster

Abstract: The antibacterial activity and efflux pump reversal of thymol and carvacrol were investigated against the Staphylococcus aureus IS-58 strain in this study, as well as their toxicity against Drosophila melanogaster. The minimum inhibitory concentration (MIC) was determined using the broth microdilution method, while efflux pump inhibition was assessed by reduction of the antibiotic and ethidium bromide (EtBr) MICs. D. melanogaster toxicity was tested using the fumigation method. Both thymol and carvacrol presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Ceftazidime antibiotic was used as a positive control. The plate was then incubated in an incubator at 37 °C for 18–24 h. MIC and MBC determination in different strains of B. pseudomallei (1026b, H777 and 316c) with broth microdilution and resazurin colorimetric assay were proposed by Silveira, et al and Teh, et al [ 65 , 66 ]. Broth microdilution was carried out with the same procedure as above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceftazidime antibiotic was used as a positive control. The plate was then incubated in an incubator at 37 °C for 18–24 h. MIC and MBC determination in different strains of B. pseudomallei (1026b, H777 and 316c) with broth microdilution and resazurin colorimetric assay were proposed by Silveira, et al and Teh, et al [ 65 , 66 ]. Broth microdilution was carried out with the same procedure as above.…”
Section: Methodsmentioning
confidence: 99%
“…For quantitative evaluation of efflux pump inhibition of AgNPs, microdilution assay was assessed with the slight modification previously described by Behdad, et al and Silverira, et al [ 28 , 65 ]. AgNPs, CAZ and EtBr were prepared in the concentration range of 0.125 to 512 µg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, thymol was shown to play an important role in enhancing the intestinal barrier function and reducing the cytokine genes expression during inflammation 8 . Moreover, it possesses a strong antimicrobial efficacy against various pathogenic bacteria 9 .…”
Section: Introductionmentioning
confidence: 99%
“…studied the antibacterial activity of thymol against S. aureus and found that it had antibacterial activity against S. aureus , and its minimum inhibitory concentration (MIC) was 72 µg mL −1 . [ 61 ] Zhang et al. in situ polymerized antifouling polysulfide (PSf)/polyethersulfone (PES) and N‐ (5‐methacrylamide‐2,3,4‐hydroxy benzyl) acrylamide (AMTHBA) composite membrane (PSf/PES‐AMTHBA membrane) by microwave technique, in which the AMTHBA as a new capsaicin derivative could realize self‐polymerization due to the CC bond and endow the PSf/PES‐AMTHBA membrane with highly effective antibacterial activity against E. coli (>85%).…”
Section: Introductionmentioning
confidence: 99%